Novel zero-current-switching PWM converters - Canesin, C. A.; Barbi, I (Institute of Electrical and Electronics Engineers (IEEE), 1997)
This paper presents a new family of pulsewidth-modulated (PWM) converters, featuring soft commutation of the semiconductors at zero current (ZC) in the transistors and zero voltage (ZV) in the rectifiers, Besides operating at constant frequency and with reduced commutation losses, these new converters have output characteristics similar to the hard-switching-PWM counterpart, which means that there is no circulating reactive energy that would cause large conduction losses, the new family of zero-current-switching (ZCS)-PWM converters is suitable for high-power applications using insulated gate bipolar transistors (IGBT's). The advantages of the new ZCS-PWM boast converter employing IGBT's, rated at 1.6 kW and operating at 20 kHz, are presented, This new ZCS operation can reduce the average total power dissipation in the semiconductors practically by half, when compared with the hard-switching method, This new ZCS-PWM boost converter is suitable for high-power applications using Ie;BT's in power-factor correction, the principle of operation, theoretical analysis, and experimental results of the new ZCS-PWM boost converter are provided in this paper to verify the performance of this new family of converters.
Keywords: DC/DC converters; power electronics; soft-commutation techniques